(untitled) (GEON Journal (Management, Organizations and Business), 2016)
Given the current regulatory requirements in governance, institutions and state enterprises should adopt quality management systems in line with the Colombian Technical Standard NTCGP 1000: 2009; among professionals who are called to contribute to that effort are public accountants; whereby a forward study aimed to identify the role of the public accountant in implementing and / or improving accounting processes in municipal decentralized institutes according to the NTCGP Villavicencio 1000: 2009. Therefore, it was conducted a descriptive study, supported by the mixed approach (qualitative and quantitative), taken as a population at seven decentralized institutions of the municipality of Villavicencio, although two samples were handled, the first were 7 public accountants who serve as internal auditor in the institutes under study; and the other to 14 public accountants who work in these institutes (2 per school) who were applied a survey form. The results allowed to establish the role of internal auditor in the implementation and / or improvement of accounting processes under study institutes according to the application of the NTCGP 1000: 2009, as well as determine the functions performed by the public accountant for the same case, and with this the role of the CPA in implementing quality management is analyzed